Methane emission reduction through hydrogen blending in a large bore 2-stroke lean-burn natural gas compressor engine - Vieira, Greg; Lorenzen, Rachel; Patterson, Mark; Olsen, Daniel (Frontiers in Fuels, 2024)
Impending and increasingly stringent emissions regulations regarding natural gas compressor engines drive the research behind blending hydrogen with natural gas to make these internal combustion engines and their combustion process more efficient. This investigation seeks to answer two fundamental questions: will blending hydrogen with natural gas reduce overall engine fuel consumption, and can greenhouse gas emissions be reduced by blending hydrogen with natural gas? A 4-cylinder Cooper–Bessemer GMV engine, housed at Colorado State University’s Powerhouse facility, was investigated for hydrogen–natural gas blending using multiple engine configurations. A lean-burn engine uses an active pre-combustion chamber as its ignition source, along with electronically activated high pressure fuel injection in the main combustion chamber. One configuration tested utilized high-pressure fuel injection and blending in hydrogen, up to 40% by volume, in both the main chamber and pre-combustion chamber fuel supplies. A second configuration, where the main combustion chamber fuel was solely natural gas and only the pre-combustion chamber received hydrogen-blended natural gas, was also tested. The final configuration to be tested used low pressure fuel injection with mechanically actuated valves in the main chamber with a traditional spark plug ignition source. All engine configurations saw reductions in methane emissions of up to 30% using blended natural gas and hydrogen. Carbon dioxide emissions were also shown to be reduced for the two configurations. A reduction in brake-specific fuel consumption of up to 2% was also seen for two configurations. These results support the hypothesis that blending hydrogen into natural gas can reduce engine total fuel consumption and reduce greenhouse gas emissions.